Estudio de prefactibilidad para la instalación de una planta procesadora de conservas de ciruela (Spondias purpurea) en almíbar - Barboza Carnero, Ximena Briset (2016)
The main objective of this project is to determine the economic, financial, social and market viability to install a factory of canned plum (Spondias purpurea) in syrup for national consumption.